Hydroxytyrosol Enrichment of Olive Leaf Extracts via Membrane Separation Processes - Costas S. Papageorgiou; Stathis Lymberopoulos; Panagiotis Bakas; Dimitris P. Zagklis; Varvara Sygouni; Christakis A. Paraskeva (Membranes, 2022)
Antioxidants isolated from plant materials, such as phenolics, have attracted a lot of attention because of their potential uses. This contributes to the idea of the biorefinery, which is a way to produce useful products from biomass waste. Olea europaea byproducts have been extensively investigated for their large contents in phenolics. Oleuropein is a phenolic compound abundant in olive leaves, with its molecule containing hydroxytyrosol, elenolic acid, and glucose. In this work, olive leaf extracts were treated using different combinations of ultrafiltration and nanofiltration membranes to assess their capacity of facilitating the production of hydroxytyrosol-enriched solutions, either by separating the initially extracted oleuropein or by separating the hydroxytyrosol produced after a hydrolysis step. The best performance was observed when an ultrafiltration membrane (UP010, 10,000 Da) was followed by a nanofiltration membrane (TS40, 200–300 Da) for the treatment of the hydrolyzed extract, increasing the purity of the final product from 25% w/w of the total extracted compounds being hydroxytyrosol when membrane processes were not used to 68% w/w.